HUBUNGAN MOTIVASI KERJA DAN KEMAMPUAN PENGUASAAN MATERI DENGAN KINERJA GURU - Samudi . (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2013)
The research objective was to analyze the relationship between motivation and the ability to master the material together with the performance of teachers in subjects Aqidah Morals. Correlational study was conducted at the junior secondary school teachers Rangkasbitung Affairs, which consists of 35 people and hypothesis testing performed with using correlation analysis. The results indicate that there is a positive relationship motivation and ability to master the material together with teacher performance.